2019
DOI: 10.3899/jrheum.190684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Apolipoprotein L1 Gene Nephropathy Variant on the Risk of Advanced Lupus Nephritis in Brazilians

Abstract: Objective Apolipoprotein L1 gene (APOL1) G1 and G2 renal risk alleles (RRA) are associated with endstage renal disease in blacks with lupus nephritis (LN). The present study determined frequencies of APOL1 RRA in nonwhite Brazilian patients with LN and controls to assess association with renal outcomes. MethodsAPOL1 RRA were genotyped in 222 healthy blood donors (controls) and 201 cases with LN from 3 outpatient clinics. Two single-nucleotide polymorphisms in the G1 (rs73885319 and rs60910145) and an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…(38) Consistently, progressive nephritis was worsened with every copy of risk allele in Brazilian AA/H lupus patients. (39) In this context, our data implicating a role for APOL1 within T cells involved in adaptive immune responses against a donor organ, demonstrate that previous data regarding R-nAPOL1 and allograft outcomes need to be reinterpreted, and its role in infiltrating inflammatory mononuclear cells in native kidney glomerulonephritis investigated.…”
Section: Discussionmentioning
confidence: 66%
“…(38) Consistently, progressive nephritis was worsened with every copy of risk allele in Brazilian AA/H lupus patients. (39) In this context, our data implicating a role for APOL1 within T cells involved in adaptive immune responses against a donor organ, demonstrate that previous data regarding R-nAPOL1 and allograft outcomes need to be reinterpreted, and its role in infiltrating inflammatory mononuclear cells in native kidney glomerulonephritis investigated.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, our observation that moderate expression of G0G1 or G0G2 caused cytotoxicity could help explain the elevated risk of APOL1 nephropathy in some carriers of one RRVs relative to carriers of G0G0. 13,14,26 Our results also raise new questions. We observed that tet induced a lower level of G0 protein relative to G2 protein in G0G2-containing HEK293 cells.…”
Section: Disclosuresmentioning
confidence: 75%
“…While single polymorphisms may not be sufficient to cause autoimmunity alone, accumulating numbers of risk variants may cause the immune system to become overwhelmed, leading to immune dysregulation [ 24 , 75 ]. Furthermore, interferon signaling upregulation inpatients with LN may trigger nephropathy associated with apolipoprotein L1 ( APOL1 ) risk-alleles (which are prevalent in individuals with Sub-Saharan African ancestry) by upregulating APOL1 mRNA expression and increasing genotype-associated disease severity [ 76 ]. Risk-associated variants in interferon-related genes have also been identified for other autoimmune diseases, including SSc, for which family history remains the strongest known risk factor [ 32 ].…”
Section: The Interferon Pathway and Its Role In Autoimmunity: Systemic Lupus Erythematosus And Beyondmentioning
confidence: 99%